2D Fabrication of Tunable Responsive Interpenetrating Polymer Networks from a Single Photoresist. (15th September 2020) - Michalek, Lukas; Bialas, Sabrina; Walden, Sarah L.; Bloesser, Fabian R.; Frisch, Hendrik; Barner‐Kowollik, Christopher
Abstract: Light‐induced curing of photoresists is a well‐established technique to fabricate polymer networks with precise control over the material properties. Herein, control is exerted over network material properties of a single polymer blend through the spatiotemporally controlled incorporation of secondary polymer networks resulting in interpenetrating polymer networks (IPNs). Light gated control over materials properties of IPNs is assessed theoretically by applying the general rule of mixture and experimentally by using a multifunctional polymer resist. The full IPNs are formed through covalent bonds, based on photocuring of the complementary photoreactive groups o‐methyl benzaldehyde (UV light) and styrylpyrene (visible light). Applied to a spin coated polymer blend of UV light curable responsive poly(4‐vinylpyridine) (P4VP) and visible light curable poly(methyl methacrylate) (PMMA), the developed platform technology not only affords spatial control over the curing of the pH‐swellable P4VP component from the polymer blend, but also allows adjustment of the extent of swelling by forming an IPN through subsequent curing of the PMMA component. Gated only by light irradiation of a polymer blend, it is possible to control IPN formation in 2D structures, which precisely adjusts the swelling behavior of the respective materials segments. Abstract : A multifunctional photoresist enabling the spatially resolved fabrication of precisely controlled full interpenetrating polymer networks as well as simultaneous tuning of the materials response of pH‐dependent swelling from a single resist is introduced. The tunability is simply achieved as a function of the color of light and the irradiation time.